Wire sweep improvement study of multi-tier palladium–copper wire bonding on low-quad flat package using low-alpha green mould compound. (8th December 2014) - Skh Ali, S. S.; Teh, S. S. H.; Ang, B. C.
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, a short-shot mould study is performed on device M in order to understand the mould-filling patterns during mould encapsulation. The wire sweep performance is evaluated for two die thicknesses, wire loop heights and various moulding compounds. Moreover, the actual length of worst swept wire is measured using various methods. Designing of experiment with four factors and three centre points is conducted on device M, which is encapsulated with low-alpha compound. The prediction profiles show that reducing the transfer time will reduce the wire sweep percentage. It is also noteworthy that wire sweep performance is strongly related to wire loop height. In addition, a thicker die gives better wire sweep performance as compared to 7 mils die, whereas decreasing the wire loop height decreases the wire sweep percentage. It can be deduced that optimum compound properties, lower wire loop height and optimum moulding parameters are the essential factors that will improve the wire sweep performance during the mould encapsulation process.